What Should I Trust? Individual Differences in Attitudes to Conflicting Information and Misinformation on COVID-19 - Filkuková, Petra; Ayton, Peter; Rand, Kim; Langguth, Johannes (Frontiers in Psychology, 2021)
The COVID-19 pandemic constitutes a novel threat and traditional and new media provide population with an abundance of information and misinformation on the topic. In the current study, we investigated who tends to trust what type of mis/information. The data was collected in Norway on the sample of 405 participants during the first wave of COVID-19 in April 2020. We focused on three types of beliefs: the belief that the threat is overrated (COVID-threat skepticism), the belief that the threat is underrated (COVID-threat belief) and the belief in misinformation on COVID-19. We studied sociodemographic factors associated with these beliefs and the interplay between attitudes to COVID-19, media consumption and prevention behaviour. All three types of beliefs were associated with distrust in information on COVID-19 provided by traditional media and distrust in authorities’ approach to the pandemic. COVID-threat skepticism was associated with male gender, decrease in news consumption after the start of the pandemic and lower levels of precautionary measures. Belief that COVID-19 threat is underrated was associated with younger age, left-wing political orientation, increase in news consumption during the pandemic and increased precautionary behaviour. In consistence with the assumptions of the theory of planned behaviour, one’s beliefs about the seriousness of the COVID-19 threat predicted the extent to which individual participants adopted precautionary health measures. Both COVID-threat skepticism and COVID-threat belief were associated with endorsement of misinformation on COVID-19. Participants who endorsed misinformation tended to have lower education, male gender, decreased news consumption, high Internet use and high trust in information provided by social media. Additionally, they tended to endorse multiple misinformation stories simultaneously, even in cases when they were contradictory. The strongest predictor for low compliance with precautionary measures was endorsement of a belief that the COVID-19 threat is overrated which at the time of the data collection was held also by a part of the experts and was featured in traditional media. The findings stress the importance of consistency in communication in situations of a public health threat.